2010
DOI: 10.1525/as.2010.50.5.990
|View full text |Cite
|
Sign up to set email alerts
|

Economic Voting in Taiwan: The Significance of Education and Lifetime Economic Experiences

Abstract: An analysis of the 1996 and 2004 Taiwan presidential elections demonstrates that the voters' overall economic experiences under the dominant Kuomintang and level of education mediated the effect of short-term economic conditions on individual vote choice before and after the first power transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Instead, what played an important role in voting decisions were voters’ evaluations of a candidate’s ability to manage the economy – along with security concerns. In an empirical analysis of Taiwan’s presidential elections of 1996 and 2004, Choi (2010) failed to discover any pervasive and consistent effect of economic voting, though her analysis did reveal a more nuanced trend. After accounting for population heterogeneity, Choi found that economic voting occurred more often among certain types of Taiwanese voters, particularly in terms of level of education and lifetime experience variables.…”
Section: Literature On Economic Voting In New Democraciesmentioning
confidence: 95%
“…Instead, what played an important role in voting decisions were voters’ evaluations of a candidate’s ability to manage the economy – along with security concerns. In an empirical analysis of Taiwan’s presidential elections of 1996 and 2004, Choi (2010) failed to discover any pervasive and consistent effect of economic voting, though her analysis did reveal a more nuanced trend. After accounting for population heterogeneity, Choi found that economic voting occurred more often among certain types of Taiwanese voters, particularly in terms of level of education and lifetime experience variables.…”
Section: Literature On Economic Voting In New Democraciesmentioning
confidence: 95%
“…Some previous studies dealt with traditional indicators of voting, such as demographic factors (Liu, 1994a;Luoh, 2001), national identity (Rigger, 2000;Shyu, 1996Shyu, , 2004Chang and Wang, 2005) and party identification (Liu, 1994b;Tan et al, 2000;Tsai and Chao, 2008). Others consider the political development and changes in Taiwan, covering various possible indicators that include economic evaluations (Hsieh et al, 1998;Choi, 2010), cross-strait relations, various types of issues (Lacy and Niou, 2012) and political performance (Ho et al, 2013). Among these, a huge portion of scholarly works has examined the extent to which national identity, partisanship and attitude toward the independence-unification issue drive voters' decisions and concluded that the China factor is the dominant predictor of Taiwan's elections.…”
Section: Modeling Issue Voting In Taiwanmentioning
confidence: 99%
“…Campbell and Miller 1957;DeVries and Tarrance 1972). Choi's analysis of voter choice in Taiwan's mixed-member system reveals that the effects of voters' differential experiences of economic growth is mediated by their education because it allows voters to link government policies with their economic fortunes (Choi 2010). However, research in the Netherlands of PR elections note that differences in education levels do not affect political participation and attitudes (Hakhverdian, van der Burg, and de Vries 2012).…”
Section: Empirical Analysismentioning
confidence: 99%